Placental bed disorders - Pijnenborg, Robert; Brosens, I. A.; Romero, Roberto (Cambridge ; New York : Cambridge University Press, 2010)
"The role of the placental bed in normal pregnancy and its complications has been intensively investigated for 50 years, following the introduction of a technique for placental bed biopsy. It is now recognized that disorders of the maternal-fetal interface in humans have been implicated in a broad range of pathologic conditions, including spontaneous abortion, preterm labor, preterm premature rupture of membranes, pre-eclampsia, intrauterine growth restriction, abruptio placentae and fetal death"--Provided by publisher.
13. Animal models of deep trophoblast invasion Robert Pijnenborg and Lisbeth Vercruysse; 14. Trophoblast-arterial interactions in vitro J. E. Cartwright and G. St J. Whitley; 15. Long-term effects of uteroplacental insufficiency in animals R. H. Lane, R. McKnight and Qi Fu; Part VI. Genetics: 16. Fertile soil or no man's land: a partial history of the placental bed David Haig; 17. Search for susceptibility genes Linda Morgan; 18. Imprinting Gudrun Moore and Sayeda Abu-Amero; Part VII. Risk Factors, Predictors and Future Management: 19. Risk factors of pre-eclampsia and SGA Rolv Skjaerven, Kari K. Melve and Lars J. Vatten; 20. Angiogenic factors and pre-eclampsia May Lee Tjoa, Eliyahu Khankin, Sarosh Rana and S. Ananth Karumanchi; 21. Assisted reproductive technology and the risk of poor pregnancy outcome Marc J. N. C. Keirse and Frans M. Helmerhorst; 22. Periconceptual and early pregnancy approach Gordon C. S. Smith; 23. New concepts and recommendations on clinical management and research Caroline Dunk, Sascha Drewlo, Leslie Proctor and John C. P. Kingdom; 24. Disorders of the placental bed in the genesis of the great obstetrical syndromes Roberto Romero, Juan Pedro Kusanovic and Chong Jai Kim; Index.
Keywords: Placenta; Placenta; Placenta Diseases; Maternal-Fetal Exchange; Placentation